Analiza pričakovanih sprememb v sponzorstvu v športu kot posledica COVID-19 - Zalaznik, Maja (Akademija MM, 2020)
Sponsorship is one of the key pillars of financing Slovenian sport. The purpose of this article is to highlight the changes in sport sponsorship and its marketing, economic and social effects in the pandemic situation. Covid-19 has strongly influenced and continues to influence the implementation of sports activities, so we are facing the challenge of how sponsors and sport properties see the changed current sponsorship situation and their attitude to future sponsorship. Therefore, a research uncovering the consequences of Covid-19 on the Slovenian sports sponsorship environment was created and implemented in May and June 2020, both through semi-structured interviews and an online questionnaire. This researchs findings suggest that changes due to Covid-19 influence sponsorship effects through changes in expectations of various sponsorship stakeholders. The changes on the consumers' side due to Covid-19 surprisingly do not influence directly the changes in expectations of various sponsorship stakeholders. Furthermore, the changes in expectations of various sponsorship stakeholders influence sponsorship effects only in the presence of sustainable communication. The study concludes with the recommendations for various stakeholders in sport sponsorship, exposing the importance of sponsors' and sport properties' cooperation with other stakeholders (consumers, society, and government). The cooperation among these stakeholders is at the heart of a newly proposed model of network relationships in sponsorship, which opens this field for future research.
Keywords: COVID-19; marketing; Slovenija; sponzorstvo; šport